FROM CHOICE OF CONCEPTS TO DESIGNING STATISTICALLY TESTABLE MODELS: ON THE CENTRALITY OF DEVELOPING CONCEPTUAL FRAMEWORKS IN RESEARCH (NAU Journal of Technology and Vocational Education, 2024)
The divergence in the application of nomological network of concepts, constructs or variables inthe report of conceptual frameworks at different levels of research is a concern to intellectual,skilled, and experienced research scholars. Sometimes, conceptual framework is erroneouslyreported as a collection of operational definition of concepts or even as a research design. Thisstudy is, therefore, in two folds: to x-ray the practical examples of more realistic and statisticallytestable conceptual models to foster less experienced researchers’ knowledge in developing andreporting conceptual framework in research; and to investigate students’ abilities in reportingconceptual framework in their research. The study adopted literature review approach with amixed method design. This study sampled postgraduate (PG) students (N = 21), drawn from afaculty in Nnamdi Azikiwe University from 2019 to 2021, as well as PG students’ certified andapproved theses/dissertations (N = 125). Observation checklist was used for the quantitativedata collection, while a semi-structured interview was used for the qualitative data collection.Percentage was employed to analyze the quantitative data, while thematic analysis was appliedfor the qualitative data. Reviews demonstrated practical guides and examples of conceptualmodels. Findings revealed poor students’ skills in designing and reporting acceptableconceptual frameworks. Hence, recommendations were made for improvement.
Keywords: Conceptual model, definition of concepts, educational research, interrelations, nomological network